Multiply (4x^2 + 2x + 1)(x - 5)

(4x^2 + 2x + 1) (x - 5) = 4x^3 - 20x^2 + 2x^2 - 10x + x - 5; = 4x^3 - 18x^2 -9x - 5

Question

Asked 7/22/2011 8:56:46 PM

Updated 10/17/2014 4:32:24 AM

1 Answer/Comment

Flagged by alfred123 [10/17/2014 4:28:41 AM], Edited by andrewpallarca [10/17/2014 4:31:57 AM], Unflagged by andrewpallarca [10/17/2014 4:32:16 AM], Edited by andrewpallarca [10/17/2014 4:32:24 AM]

Rating

3

(4x^2 + 2x + 1) (x - 5)

= 4x^3 - 20x^2 + 2x^2 - 10x + x - 5;

= 4x^3 - 18x^2 -9x - 5

= 4x^3 - 20x^2 + 2x^2 - 10x + x - 5;

= 4x^3 - 18x^2 -9x - 5

Added 10/17/2014 4:28:15 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [10/17/2014 4:31:21 AM]

Find the equation of the line that contains the point (2, -3) and has slope 4 **Weegy:** A.-3 **User:** Find the equation of the line that contains the point (2, -3) and has slope 4 (More)

Question

Expert Answered

Updated 6/27/2014 11:25:31 AM

1 Answer/Comment

The equation of the line that contains the point (2, -3) and has slope 4 is y = 4x - 11

y = mx + b or

-3 = 4 * 2+ b:

-b = 8 + 3; -b = 11; b = -11

y = mx + b or

-3 = 4 * 2+ b:

-b = 8 + 3; -b = 11; b = -11

Added 6/27/2014 11:25:29 AM

This answer has been confirmed as correct and helpful.

expand (6x + 1)^2
**Weegy:** check this link hope this helps :) (More)

Question

Expert Answered

Updated 6/27/2014 11:18:46 AM

1 Answer/Comment

(6x + 1)^2

= (6x + 1)(6x + 1)

= 36x^2 + 6x + 6x + 1

= 36x^2 + 12x + 1

= (6x + 1)(6x + 1)

= 36x^2 + 6x + 6x + 1

= 36x^2 + 12x + 1

Added 6/27/2014 11:18:46 AM

This answer has been confirmed as correct and helpful.

27,937,308

questions answered

There are no comments.